Growth inhibition of nematophagous and entomopathogenic fungi by leaf litter and soil containing phenols - Lopez-Llorca, L. V.; Olivares-Bernabeu, C. (Mycological Research, 1997)
In a soil survey, nematophagous fungi were recovered less from agar plates sprinkled with forest soil (Quercus ilex subsp. rotundifolia) than from those incubated with agricultural (Citrus orchards) soil. Nematodes were present in all soils. The organic matter was higher in forest soils. Water extracts from forest soils with high levels of phenols, leaf litter and Q. rotundifolia fresh leaves aﬀected the development and growth of common species of nematophagous and entomopathogenic fungi. These results show that phenolics from leaf letter could play an important role in the ecology and biology of these invertebrate pathogens in soil.
Keywords: agricultural soil; entomopathogenic fungi; forest soil; fungal growth (voyant); leaf litter; nematophagous fungi; phenolic compounds; quercus ilex ssp rotundifolia

Growth inhibition of nematophagous and entomopathogenic fungi by leaf litter and soil containing phenols - Lopez-Llorca, L V; Olivares-Bernabeu, C (Mycological Research, 1997)
In a soil survey, nematophagous fungi were recovered less from agar plates sprinkled with forest soil (Quercus ilex subsp. rotundifolia) than from those incubated with agricultural (Citrus orchards) soil. Nematodes were present in all soils. The organic matter was higher in forest soils. Water extracts from forest soils with high levels of phenols, leaf litter and Q. rotundifolia fresh leaves aﬀected the development and growth of common species of nematophagous and entomopathogenic fungi. These results show that phenolics from leaf letter could play an important role in the ecology and biology of these invertebrate pathogens in soil.
Keywords: agricultural soil; entomopathogenic fungi; forest soil; fungal growth (voyant); leaf litter; nematophagous fungi; phenolic compounds; quercus ilex ssp rotundifolia